Social-economic estimation of competitive positions formation of Ukrainian regional residential real estate markets - Strishenets, Olena M.; Pavlov, Kostiantyn V.; Стрішенець, Олена Миколаївна; Павлов, Костянтин Володимирович (Publishing House “Baltija Publishing”, 2018)
In the conditions of obtaining new market economy-oriented vibrancy with the pursuit of integration into the European community, the issues of regional self-development on the principles of transparent compe- tition are becoming increasingly topical. The lack of effective approaches to the implementation of the competition regulation mechanism in the regional residential real estate markets caused a significant construction sector monopolisation, the emergence of its development disproportions and social tensions within the population. The regional policy formation for the competitive relations regulation in construction should take place in compliance with state priorities. This, conversely, leads to the study of issues related to the assessment of the social-economic potential of the regions and the degree of the regional residential real estate markets com- petitiveness, taking into account fundamental research and analysis of the developed national theoretical and practical approaches. Consequently, the objectivity of the social-economic assessment of the competitive environ- ment of the country regions depends on the immediate regional market sys- tems functioning, including the residential real estate market.
Соціально-економічна оцінка формування конкурентних позицій регіональних ринків житлової нерухомості України
Keywords: Social-economic estimation; regional residential real estate markets; real estate markets